Request of laboratory liver tests in primary care in Spain. Issue 10 (October 2015) - Salinas, Maria; López-Garrigós, Maite; Flores, Emilio; Uris, Joaquín; Leiva-Salinas, Carlos
<x xml:space="preserve">Abstract</x> Aims Liver laboratory tests are used to screen for liver disease, suggest the underlying cause, estimate the severity, assess prognosis, and monitor the efficacy of therapy. The aim of this study was to compare the liver laboratory tests requesting patterns by GPs in Spain, according to geographic and hospital characteristics, to investigate the degree of requesting appropriateness. Materials and methods One hundred and forty-one clinical laboratories were invited to participate from diverse regions across Spain. They filed out the number of laboratory liver tests requested by GPs for the year 2012. Two types of appropriateness indicators were calculated: every test request per 1000 inhabitants or ratios of related tests requests. The indicator results obtained were compared between the different hospitals, according to their setting, location, and management. The savings generated, if each area would have achieved indicator targets, were calculated. Results We recruited 76 laboratories covering a population of 17 679 195 inhabitants. GPs requested 20 916 780 laboratory liver tests in the year 2012. No differences were obtained according to their setting. Lactate dehydrogenase and direct bilirubin per 1000 inhabitants were significantly higher in institutions with private management. Largest differences were observed between communities. Nine, 31, 0, and 13 laboratories, respectively, achieved the aspartate aminotransferase, lactate dehydrogenase, γ-glutamyl transpeptidase, and total bilirubin-related alanine aminotransferase indicator targets. Reaching ratios would have resulted in savings of [Euro sign]1 028 468. Conclusion There was a high variability in the request of liver tests. This emphasizes the need to implement interventions to improve appropriate use of liver tests.